Predicting Successful Intended Vaginal Delivery After Previous Cesarean Section. Issue 2 (June 2015) - Schoorel, E.N.; Melman, S.; van Kuijk, S.M.; Grobman, W.A.; Kwee, A.; Mol, B.W.; Nijhuis, J.G.; Smits, L.J.; Aardenburg, R.; de Boer, K.; Delemarre, F.M.; van Dooren, I.M.; et al.
<x xml:space="preserve">Abstract</x> (BJOG. 2014;121(7):840–847)